Factors Predicting Myocardial Recovery After Hospitalization for De Novo Heart Failure with Reduced Left Ventricular Ejection Fraction: Results from the COMFE Registry - Víctor Donoso-Trenado; Óscar Otero-García; Raquel López-Vilella; Pablo de la Fuente López; Julia Martínez-Solé; Carlos Yebra-Pimentel Brea; Borja Guerrero-Cervera; Javier Adarraga Gómez; Sara Huélamo-Montoro; Guillermo Gallego-Latorre; David García-Vega; Inés Gómez-Otero; et al. (Biomedicines)
Background/Objectives: Patients hospitalized for de novo heart failure with reduced ejection fraction (HFrEF) may experience improvement in left ventricular function, a phenomenon associated with improved morbidity and mortality outcomes. However, the factors influencing this improvement remain unclear. This study aimed to investigate the association between clinical and therapeutic factors and short-term improvement or recovery of left ventricular ejection fraction (LVEF) in patients hospitalized with newly diagnosed heart failure with reduced ejection fraction (HFrEF). Methods: This was a prospective observational study conducted in two referral centers in Spain. All patients admitted with de novo HFrEF between March 2021 and December 2023 were included. Improved myocardial function (HFimpEF) was defined as an initial LVEF ≤ 40% and a follow-up echocardiogram showing LVEF > 40%, with an increase of ≥10 points from baseline. Results: In total, 157 patients (63.3%) met the criteria for HFimpEF. Among the various etiologies of heart failure, significant differences were found between groups for tachycardiomyopathy (HFimpEF: 29.3% vs. non-HFimpEF: 13.1%, p = 0.006), valvular (HFimpEF: 7.6% vs. non-HFimpEF: 1.1%, p = 0.05), and ischemic (HFimpEF: 17.2% vs. non-HFimpEF: 43.9%, p < 0.0001) etiologies. Multivariate analysis showed that non-ischemic etiologies significantly favored myocardial improvement compared to ischemic cardiomyopathy. NT-proBNP values were consistently higher in the non-HFimpEF group at all time points measured with statistically significant differences, except at admission. Event-free survival curves (hospitalization for HF, worsening HF, and all-cause mortality) diverged early, showing statistically significant differences between groups. Conclusions: Overall, 63% of patients hospitalized for de novo HFrEF achieved myocardial improvement within an average of 3–4 months, with improvement favored by valvular and tachycardiomyopathy etiologies. This improvement has a significant prognostic impact.